Uma análise lexicográfica dos elementos coesivos sequenciais do Português para a elaboração de uma proposta de definição: um estudo com base em corpus - Grama, Daniela Faria (2016)
This research analyzes how some of the portuguese sequential cohesive elements are defined in four dictionaries: a) Novíssimo Aulete – dicionário contemporâneo da língua portuguesa, b) Dicionário Houaiss Conciso, c) Aulete Digital e d) Dicionário eletrônico Houaiss da língua portuguesa. The dictionaries a and b are considered as Type 4, that is, directed to students of first to third year of high school, and the dictionaries c and d are thesaurus. The aim is to analyze if the school dictionaries present significant differences from the thesaurus dictionaries and develop a definition proposed for the sequential cohesive elements to lexicographers who are engaged in producing dictionaries that are used by students of the last years of the high school. Knowing that students must complete the high school with developed writing skills, we ask ourselves: are the dictionaries a support for the writing practice and, in particular, for the use of elements that help sequential cohesion of a text? To select the cohesive elements investigated in our research, we used the methodology / approach of Corpus Linguistics and prepared a corpus of essays with written textual productions which were taken from the site UOL Educação and refer to the period 2009-2014. After the corpus analysis has been done, we obtained a list of sequential cohesion elements used in the texts and a list of the same elements that have been used improperly, being the last one the criterion established to define the target words analysis in dictionaries. To get the results of this research, we used the theoretical contributions from the Lexicography, Pedagogical Lexicography, Text Linguistics and Argumentative Semantics.